Mechanistic modeling of gas-liquid two-phase flow in pipes - Shoham, Ovadia; Society of Petroleum Engineers of AIME. (Richardson, TX : Society of Petroleum Engineers, 2006)
The objectives of this book are twofold: to provide insight and understanding of two-phase flow phenomena and to develop analytical tools for either designing two-phase flow systems or conducting research in this area. The traditional approach for two-phase flow prediction has been the empirical approach, which was based on the development of an empirical correlation from experimental data. This book presents the recent approach, in which mathematical mechanistic models are developed, based on the physical phenomena, for the prediction of two-phase flow behavior. The models can be verified and refined with limited experimental data. However, as these models incorporate the physical phenomena and the important flow variables, they can be extended to different operational conditions and can enable scaleup with significant confidence.
Fundamentals of two-phase flow -- Early black-box models -- Flow in pipelines -- Flow in wellbores -- Flow in inclined pipes -- Two-phase-flow heat transfer -- Introduction to transient flow and application examples -- Nomenclature -- References -- Suggested reading -- Indexes.
Includes index.
Includes bibliographical references (p. [365]-374).
ME
English
Keywords: Two-phase flow; Multiphase flow; Fluid dynamics; Two-phase flow -- Mathematical models